Properties and Applications of the Metal-Insulator-Semiconductor (MIS) Tunnel Diode - Green, Andrew Martin (My University, 1974)
This work describes a theoretical and experimental investigation into the electrical properties and possible device applications of the three layer Metal-Insulator-Semiconductor (MIS) structure when the insulating layer is very thin (<60A). Under these conditions, current can flow between the metal and the semiconductor by quantum mechanical tunneling processes. This work is limited to the case where the semiconductor is not degenerately doped.
To aid in the discussion of the properties of this structure, its electrical behaviour is simulated by describing the transport processes through the semiconductor and the insulator regions mathematically and solving the resulting system of mathematical equation numerically. Solutions for both the AC and DC properties of the structure are obtained in this way. Using these solutions as a guideline, a general theoretical framework is established which allows the device properties to be predicted when parameters such as the work function of the metal contact, the insulator thickness, the properties of surface states at the insulator-semiconductor (IS) interface, the device temperature, and the dopant type in the semiconductor are varied. Particular importance is placed upon the charge conditions in the semiconductor at the IS interface under zero bias conditions. Depending upon whether this region is strongly inverted, depleted, or accumulated, the dominant component of the diode current tends to flow between the metal and the minority carrier energy band, surface state levels, and the majority carrier energy band in the semiconductor respectively. Correspondingly, the devices are classified as minority carrier, surface state, and majority carrier diodes. In addition to this classification, a distinction between "equilibrium" and "non-equilibrium" devices is made. In the former, the insulator layer is thick and the device currents small while in the latter, this layer is thinner and the enhanced current flows cause the semiconductor to depart significantly from thermal equilibrium. Experimental measurements upon the metal-silicon dioxide-silicon system are used to demonstrate the validity of this theory and also demonstrate the utility of the classification scheme described.
Non-equilibrium diodes are of particular interest because of their possible device applications. Majority carrier non-equilibrium devices exhibit current multiplication properties which are discussed theoretically and measured experimentally. These make the devices of interest in transistor structures and in such applications as photo-diodes with internal multiplication properties. Minority carrier non-equilibrium devices are shown both theoretically and experimentally to possess properties similar to p-n junction diodes under reverse and small to moderate forward bias. Since they are considerably simpler to fabricate, they have possible application as replacing junction devices in a number of applications such as those as injecting contacts, photo-diodes, or members of photo-diode arrays. One particularly promising application is to direct energy conversion using the electron-or photo-voltaic effect. For an energy conversion situation using the radioisotope Pm147 as the primary energy source it is demonstrated that the predicted higher conversion efficiency of the MIS tunnel diode compared to the p-n junction diode can be experimentally realized.
Keywords: Electrical and Electronics; Electrical and Electronics